Kinin B1 receptor antagonist BI113823 reduces allergen-induced airway inflammation and mucus secretion in mice. (February 2016) - Gurusamy, Malarvizhi; Nasseri, Saeed; Lee, Hana; Jung, Birgit; Lee, Dongwon; Khang, Gilson; Abraham, William M.; Doods, Henri; Wu, Dongmei
Graphical abstract: Abstract: Kinin B1 receptors are implicated in asthmatic airway inflammation. Here we tested this hypothesis by examining the anti-inflammatory effects of BI113823, a novel non-peptide orally active kinin B1 receptor antagonist in mice sensitized to ovalbumin (OVA). Male Balb-c mice were randomly assigned to four study groups: (1) control, (2) OVA + vehicle, (3) OVA + BI113823, (4) OVA + dexamethasone. Mice were sensitized intraperitoneally with 75 μg ovalbumin on days 1 and 8. On days 15–17, mice were challenged intranasally with 50 μg of ovalbumin. Mice received vehicle, BI113823, or dexamethasone (positive control) on days 16–18. On day 19, bronchoalveolar lavage (BAL) and lung tissue were collected for biochemical and immuno-histological analysis. Compared to controls treatment with BI113823 significantly reduced the numbers of BAL eosinophils, macrophages, neutrophils and lymphocytes by 58.3%, 61.1%, 66.4% and 56.0%, respectively. Mice treated with dexamethasone showed similar reductions in BAL cells. Treatment with BI113823 and dexamethasone also significantly reduced total protein content, IgE, TNF-α and IL-1β in lavage fluid, reduced myeloperoxidase activity, mucus secretion in lung tissues, and reduced the expression of B1 receptors, matrix metalloproteinase (MMP)-2 and cyclooxygenase (COX)-2 compared to vehicle-treated mice. Only BI113823 reduced MMP-9 and inducible nitric oxide synthase (iNOS). BI113823 effectively reduced OVA-induced inflammatory cell, mediator and signaling pathways equal to or greater than that seen with steroids in a mouse asthma model. BI113823 might be useful in modulating inflammation in asthma.